Evidence for neurotoxicity associated with amoxicillin in juvenile rats. (August 2016) - Atli, O; Demir-Ozkay, U; Ilgin, S; Aydin, TH; Akbulut, EN; Sener, E
Amoxicillin (AMX) is one of the most commonly prescribed antibiotics for children, and childhood is the period to have the highest risk for toxicity cases including drug-induced adverse reactions. Some neurological adverse effects (anxiety, hyperactivity, confusion, convulsions, and behavioral changes) have been reported related to AMX treatment. In the present study, we aimed to determine the neurotoxic effects of AMX administration at clinically relevant doses in female juvenile rats. AMX was administered in single oral daily doses of 25 and 50 mg/kg for 14 days. According to our results, while AMX administration caused a significant increase in the immobility time of animals, swimming time of these animals significantly decreased. AMX administration significantly reduced the onset of pentylenetetrazole-induced convulsions. The serotonin levels of brain tissues in the AMX-administered groups were decreased significantly, which is thought to be related to depression. The glutamate levels in brain tissues increased significantly in AMX-administered groups, which is thought to be related to convulsion. Otherwise, superoxide dismutase and catalase activities were significantly decreased in brain tissues of AMX-administered groups. In conclusion, AMX administration triggered depression and shortened the time of the appearance of first seizure in juvenile rats. Also, altered brain neurotransmitter levels and increased oxidative stress observed in our study were thought to be the possible underlying mechanisms of AMX-induced neurotoxicity.